RI 6704 Explosive-Expansion Center-Hole Anchor - Edward W. Parsons (The National Institute for Occupational Safety and Health (NIOSH), 1965)
The explosive-expansion center-hole anchor was designed and developed for the specific purpose of use as a component of an instrument system that measures differential ground movement within a small drill hole in rock. Such anchors should have an unobstructed center hole, should be installed without a twisting action which could tangle connecting wires, and should be capable of being installed at depths in excess of 100 feet. The anchor has a thick-walled center tube and a thin-walled outer tube. Low-energy detonating cord, wrapped around the center tube and detonated with a mild end primer, expands the outer tube to produce anchorage. The explosive-expansion center-hole anchor can be installed easily in drill holes of any inclination but cannot be installed under water. Centering of the anchor is critical with regard to its subsequent holding power. The anchor is safe to make and handle.